2018
DOI: 10.1371/journal.pone.0208108
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the antibacterial activity of Bald’s eyesalve against drug resistant Staphylococcus aureus and Pseudomonas aeruginosa

Abstract: Bald’s eyesalve is an Anglo-Saxon medicinal remedy that has been used through ancient times to treat eye sty infections and may represent a source of ancientbiotics. This study assessed the efficacy of Bald’s eyesalve against several strains of Staphylococcus aureus and Pseudomonas aeruginosa, including a multi-drug resistant phenotype, and identified the principal compound conveying antibacterial activity. Bald’s eyesalve formulations were produced by combining garlic, onion or leek, wine, bovine bile, and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Our results against planktonic cultures of S. aureus and P. aeruginosa align with a report by Fuchs et al 2018, that garlic alone, and specifically allicin, accounts for the majority of the planktonic activity of Bald’s remedy. Allicin is a defensive compound that is converted from alliin by the enzyme alliinase, upon damage to the plant tissue.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results against planktonic cultures of S. aureus and P. aeruginosa align with a report by Fuchs et al 2018, that garlic alone, and specifically allicin, accounts for the majority of the planktonic activity of Bald’s remedy. Allicin is a defensive compound that is converted from alliin by the enzyme alliinase, upon damage to the plant tissue.…”
Section: Discussionsupporting
confidence: 91%
“…Our initial work indicated that all four ingredients in ESO were required to kill biofilms of S. aureus Newman in synthetic wound biofilms (20). A recent publication by Fuchs et al (2018; (21)) concluded that the bactericidal activity of ESO was due to the presence of allicin from garlic, however, the Fuchs et al study only investigated planktonic killing in standard Mueller-Hinton Broth (MHB). It is well known that planktonic cultures of bacteria can be up to 1,000 times more sensitive to antibiotics than the same isolates grown as biofilms (7), and that antibiotic sensitivity is highly dependent on growth medium (31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include oils from Cupressus sempervirens (Cypress) and Commiphora species (myrrh), being used to treat colds, coughs, and inflammation (8), and Artemisia annua (Artemisin) used to treat malaria (9). Bald’s eyesalve has previously been shown to possess antibacterial activity against Staphylococcus aureus in planktonic cultures and biofilms (10), and against Pseudomonas aeruginosa in planktonic cultures (11). A recent study from our laboratory found that Bald’s eyesalve had antimicrobial activity against a range of Gram-positive and Gram-negative organisms in planktonic cultures and biofilms (12).…”
Section: Introductionmentioning
confidence: 99%